PENDAMPINGAN SERTIFIKASI HALAL DAN SUPPORT BANNER SEBAGAI PENINGKATAN DAYA SAING PADA UMKM DI DESA SUKOPURO - A Rizki Munshif Sya’bani; Arsita Indriani; Salman Alfarizi; Hayati Ridha; Bilqis Nabila; Sharfina Nur Amalina (As-Sidanah, 2024)
UMKM are an important component in the economic structure in Indonesia, because of their significant presence in the economy and provide broad employment opportunities for enthusiasts. However, there are still many UMKM players who do not understand efforts to increase competitiveness, one of which is the need to have a halal certificate and also the importance of branding UMKM products. Therefore, this Student Work Lecture activity aims to be able to contribute to providing halal certification assistance and making banners for UMKM in Sukopuro Village, Jabung, Malang Regency. Assistance activities are carried out using the ABCD (Asset Base Community Developmenet) approach method. The results of this community service activity are assistance in registering halal certification and supporting banners for UMKM.